The Psychosocial Therapy for Schizophrenia : A Systematic Review - Dharma, I Dewa Gede Candra; Beo, Yosef Andrian (Future Science, 2022)
Schizophrenia was a type of mental disorder with distortion characteristic in thought, perception, emotion, language, self-feeling, and behavior which could be cured when it was given a proper treatment and effective psychosocial therapy which aimed to increase life skill and train social skill. This article was aimed to identify which psychosocial therapy which could be given to schizophrenia patients when they were out from a mental hospital to prepare their selves back to society. The literature reviews were taken from four databases as ScienceDirect, CAB Direct, EBSCOhost, and SpringerLink by using following keywords: psychosocial therapy, schizophrenia therapy, and community therapy. Prefered Reporting Items For Sytematic Riviews (PRISMA) method was used to select the data by determining inclusion and exclusion criteria. Based on the criteria, the researcher defined 15 articles from 2016 – 2021 to be further analyzed. The psychosocial therapy was a main focus which must be concerned on schizophrenia patients while they were out from the mental hospital or undergoing a treatment in Public health center to prepare their selves to be back to the community. There were several kinds of psychosocial therapy that could be implemented to schizophrenia patients as cognitive therapy, psycho education, community therapy, or therapy in a combination with other therapies. Moreover, the accessibility of rehabilitation center was the most important aspect to be existed in order to support the therapy implementation for schizophrenia patients while they were out from the mental hospital and back to their family and community.